On the behavior of roots of trinomial equations - Botta, V. [UNESP]; da Silva, J. V. [UNESP] (Springer Nature, 2019)
The main purpose of this paper is to investigate the distribution, simplicity and monotonicity of the roots of a class of trinomial equations that appears in certain financial mathematics problems. Furthermore, we show that it is possible to decompose some classes of trinomial equations into polynomials generated by a three term recurrence relation.
Keywords: financial mathematics; root; trinomial equation